2018
DOI: 10.5539/ijel.v8n6p328
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Metacognitive Strategies on Jordanian EFL Learners’ Writing Performance

Abstract: One of the most challenging aspects of foreign language learning is writing. Writing is the most demanding and complicated aspect of language system. Writing requires the collective effort of orthographic, graphomotor and other linguistic skills with the inclusion of semantics, syntax, spelling, and writing conventions without being restricted to the aforementioned skills. The Improvement of cognitive psychology, metacognition has drawn the focus of an increasing number of researchers' and paved way for recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In the findings of the present study, it was already mentioned that peer assessment helped learners become aware of the Education Research International monitoring strategy after receiving treatment. In a study [22], examining the impact of metacognition on the writing skills of English learners, researchers found that metacognitive strategies improved the writing skills of secondary school students. Generally, these studies indicated that metacognitive strategy is a useful way of writing skills, and finding ways like peer assessment and self-assessment to improve metacognition could be effective in the improvement of different language skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the findings of the present study, it was already mentioned that peer assessment helped learners become aware of the Education Research International monitoring strategy after receiving treatment. In a study [22], examining the impact of metacognition on the writing skills of English learners, researchers found that metacognitive strategies improved the writing skills of secondary school students. Generally, these studies indicated that metacognitive strategy is a useful way of writing skills, and finding ways like peer assessment and self-assessment to improve metacognition could be effective in the improvement of different language skills.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Al-Jarrah et al [22] examined the effect of metacognition on the writing skills of 44 secondary school students in Jordan. Researchers used pretest, posttest, and delayed posttest to examine the metacognition effect.…”
Section: Peer Assessment and Metacognitive Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies focus on a specific language skill. Al-Jarrah et al’s (2018) study, for instance, demonstrated the effectiveness of SBI concerning metacognitive strategies in improving learners’ writing competence. In addition to improving learners’ specific language skills, SBI also devotes to helping to develop learners’ beliefs that benefits their language learning.…”
Section: Introductionmentioning
confidence: 89%